Estudo das taxas reprodutivas e capturabilidade de baleias jubarte Megaptera novaeangliae (BOROWSKI, 1781; CETACEA: MYSTICETI), em sua principal área de concentração para reprodução na costa brasileira (Banco dos Abrolhos, Bahia, Brasil) - Godoy, Maria Luiza Motta Pacheco de (Universidade Federal de Juiz de Fora (UFJF), 2007)
The commercial whaling developed during the XX century dizimated many humpback whale (Megaptera novaeangliae) populations of Southern Hemisphere. One of them, found around South Georgia Island, is known to migrate to the Brazilian coast during the breeding season. The intense past exploration have resulted in ecological trends such as changes in reproductive rates. Photo-identification and ship surveys conducted at Abrolhos Bank from 1989 to 2003 were analyzed with the main goal to evaluate how these values are changing over the years. The crude birth rate differed significantly by year (Cruise surveys: Mean = 0,192 ± 0,05; G Test, p<0,001/ Photo-identification: Mean = 0,054 ± 0,012; G Test, p<0,001). Nevertheless, the calving rate showed no significant differences by year (Mean = 0,87± 0,12; G Test; p>0,05). This study verified significant differences in catchability related to the reproductive status (H = 25,01; p = 0,003) and number of individuals composing a group. Associations with three or less individuals showed higher catchability compared to groups composed by four and more animals (U = 16; p<0,05). The highest probability of a whale from Abrolhos Bank be photo-identified was in a group composed by three adults. A caça comercial desenvolvida no início do século XX dizimou populações de baleias jubarte (Megaptera novaeangliae) em muitas regiões do oceano Antártico, entre elas os arredores da ilha Geórgia do Sul. Recentemente, este local foi confirmado como destino migratório das jubartes que se concentram no banco dos Abrolhos, situado entre a Bahia e Espírito Santo, durante a estação de reprodução. Embora em fase de crescimento populacional, este estoque pode apresentar sobrecargas ecológicas tais como alterações na taxa de nascimentos em conseqüência da intensa exploração a que foram submetidos. Este estudo objetivou o levantamento de informações a respeito das taxas brutas de nascimento e de fertilidade de baleias jubarte entre os anos de 1992 e 2003. Como parte desse trabalho, ...